Bicycle commuting beyond short distances: built environment, socio-demographic factors and type of bicycle influencing the choice to cycle to three university campuses. - Rybels, Stijn; Vanoutrive, Thomas; Corradi, David; Coppens, Tom (European Journal of Transport and Infrastructure Research, 2024)
Promoting cycling as commuting mode has gained interest due to the increasing consensus among policymakers, supported by scientific evidence on the benefits of cycling. While the convenience of cycling as main commuting mode tends to decrease as commuting distances increase, emerging travel modes such as e-bikes and speedpedelecs, and the promotion and development of cycle highways could overcome distance as barrier to commute by bicycle. This paper uses the commuting data (n= 6,425) of a mid-size university in Belgium to identify the commuter characteristics and built environment determinants that are associated with a higher prevalence of battery-assisted and long-distance regular cycling through a multinomial logistic regression analysis. The case offers a wide range of workplaces and residential locations in terms of density as well as other built environment factors. The paper discusses the potential of long-distance bicycle commuting to shift individuals from motorized commuting towards more active modes. The results suggest that e-bikes and speedpedelecs offer broader geographical reach and appeal to a more diverse demographic. The development of a comprehensive network of cycle highways, emphasizing safety and separation, holds promise for promoting these types of bicycles. Additionally, mixed-use dense (peri-)urban neighbourhoods can stimulate cycling commuting also beyond short distances.